Emergency Communication and Quick Seismic Damage Investigation Based on Smartphone - Ruicong Han; Xuefeng Zhao; Yan Yu; Quanhua Guan; Deli Peng; Mingchu Li; Jinping Ou (Advances in Materials Science and Engineering)
The communications in the quake-hit area are always cut off from the outside after the earthquake, and the traditional seismic field investigation method calls for immense time to accomplish house-to-house investigation, which goes against timeliness of the emergency rescue. In this paper, an emergency communication and quick seismic damage investigation method based on smartphone is proposed. Towards this, an application, E-Explorer, on iOS platform is initially developed. First, in the emergency communication module, the communication is available by using the Multipeer Connectivity Framework technology even without external network. A series of validation experiments are simulated without external network, and the results prove convincing. This module enhances the possibility of communication and increases the chances for rescue. Second, in the damage investigation module, E-Explorer integrates the functions of questionnaire and picture collection for damage phenomenon recording and image acquisition, following an intensity evaluation method according to seismic index. Last, a website, which provides guidance for rescue workers and collects damage information for quick intensity evaluation, is being built.